SORPTION-SPECTROPHOTOMETRIC DETERMINATION OF CU(II) ION (Scientific journal of the Fergana State University, 2024)
The interaction of copper (II) ions with immobilized nitrozin yellow on natural fiber silk fibroin as a sorbent was studied. This work presents a selective and highly efficient analytical reagent for the determination of copper (II) ions. Initially, the properties of immobilizing nitrozin yellow onto silk fibroin were explored, followed by the analytical characteristics of complex formation with the metal ion using a spectrophotometric method. The resulting complex was studied using various spectroscopic and electrochemical methods. The process of determining copper (II) ions using immobilized nitrozin yellow on silk fibroin fibers has advantages such as selectivity, low detection limit, reproducibility of results, rapidity, and ease of regeneration. The spectroscopic signals of the reagent and the complex formed with copper (II) ions were found at 480 nm and 540 nm, respectively. Additionally, in the developed method, the lower detection limit of copper (II) was determined to be no more than 0.2 µg/ml, with the relative standard deviation value shown to be less than 0.033.